Kemampuan Ampas Tahu dalam Proses Koagulasi Logam Berat Krom (Cr) pada Limbah Cair Pabrik Penyamakan Kulit - Indah Murwani Yulianti; Junina Yulianti Baun; Fransiscus Sinung Pranata (Jurnal Ilmu Lingkungan, 2023)
AbstractLeather tannery wastewater is a waste from the production of raw leather into leather that has been tanned using chrome tanning material. In the production process, the liquid waste still contains around 20-40% chromium because during the production, not all of the chromium material is bound to the skin when discharged into the environment and because of that, it can cause lung cancer, skin cancer, renal tubular necrosis, skin hyperpigmentation even death. Based on the results of the characteristics of the tannery liquid waste using AAS (Atomic Absorption Spectrometry), it can be seen that the content of heavy metal chromium (Cr) is 501 mg / l. Tofu dregs is a biosorbent material because it contains protein which can bind heavy metals. The protein content in tofu dregs was 20.63%. The experimental design used in this study was factorial completely randomized design (RALF) with 2 factors, namely variations in tofu pulp weight (100 mg, 300 mg and 500 mg) and variations in contact time (60 minutes, 90 minutes and 120 minutes). Tofu dregs have the ability to reduce levels of heavy metal chromium (Cr) from 35.97% to 66.43% which means they have the same ability as alum on the market. The optimum weight of tofu dregs to reduce heavy metal chromium (Cr) is a variation of 100mg. The optimum contact time of the heavy metal chrome (Cr)  to bind tofu dregs is 90 minutes.